Exploring mobile pricing strategies and innovations in the Thai mobile communications market - Chalita Srinuan; Pratompong Srinuan; Erik Bohlin (International Telecommunications Society (ITS), 2012)
This paper aims to explore the price plans offered by Thai mobile operators and analyse the role of demand characteristics in the development of new price plans. The paper also shows how demand affects a firm's degree of innovativeness in terms of the number of new price plans. The empirical qualitative analysis is based on an original data set from several secondary data sources and includes all the price plans offered in the history of the Thai mobile communications market between 2002 and 2010. The results show that mobile operators have introduced several innovative price plans to attract and retain their consumers. Although a greater number of price plans can increase competition among operators, some have complex combinations that may lead to confusion for consumers. A price comparison programme should therefore be implemented by the telecom regulator to ensure that consumers receive correct and complete information about the price plans. Most studies, by far, have not extensively discussed this mobile communications market in detail and the effect of innovation on competition between firms in the mobile communications industry, in particular the development of innovation in developing countries.
Keywords: 330; pricing strategies; mobile communications market; innovation; Thailand